Expressions in the Description of Orthodox Christianity in Kronika, to jest historyja świata by Marcin Bielski (1564) - Kozaryn, Dorota (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The article examines the linguistic ways of describing Orthodoxy by Marcin Bielski in the third edition of his Chronicle, dated to 1564. The analyses show that Bielski uses various names for this religion, distinguishing between the Greek and Ruthenian faith, that he names the Orthodox in many ways, provides details about the manner of baptism, the Eucharist, places of worship and the veneration of saints, and the mission of St. Cyril and Methodius, and evokes the reasons for the split of both churches or attempts to resolve it.